How to make and justify a decision: the analytic hierarchy process. Part 1. Examples and Applications - Saaty, T.L. (Системні дослідження та інформаційні технології, 2002)
We describe and discuss a logical approach, the Analytic Hierarchy Process (AHP), that can be used to make decisions. It involves breaking the problem down into finer and finer parts so that one is called upon to give a judgment comparing only a pair of issues in each judgment. Розглядається та обговорюється логічний підхід — аналітично-ієрархічний процес (АІП), який можна застосовувати до прийняття рішень. Він полягає в поділенні проблеми на все дрібніші і дрібніші частки, поки кожне рішення не буде зведено до порівняння двох альтернатив. Описывается и обсуждается логический подход — аналитическо-иерархический процесс (АИП), который может применяться для принятия решений. Он состоит в делении проблемы на все более и более мелкие части до тех пор, пока каждое решение не сведется к сравнительной оценке двух альтернатив.